Analisis Pengaruh Pengetahuan, Kepribadian, dan Reputasi Terhadap Keputusan Masyarakat Memilih Bank Syariah di Banda Aceh - Akmal Riza; Lukman Hakim; Eliana Eliana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
The study was conducted to determine the effect of knowledge, personality and reputation on people's decisions to choose Islamic banks. The research subjects were all people of Banda Aceh city in early 2020 as many as 270.321 people using the Slovin formula with cluster random sampling technique representing 9 sub districts total 100 respondents using Islamic banking services. The data analysis technique uses linear regression to answer the proposed hypothesis. The results show that all independent variables of knowledge, personality and reputation influence the variables related to the customers decision to choose Islamic bank in the city of Banda Aceh.